Ectomycorrhizal fungi and their enzymes in soils: is there enough evidence for their role as facultative soil saprotrophs? - Baldrian, Petr (Oecologia, 2009)
Although ectomycorrhizal (ECM) fungi are generally regarded as dependent upon the supply of carbon from their plant hosts, some recent papers have postulated a role for these fungi in the saprotrophic acquisition of carbon from soil. This theory was mainly based on the increase in enzymatic activity during periods of low photosynthate supply from tree hosts and emergence of the theory has led to a question about the overall influence of saprotrophy by ECM fungi on soil carbon turnover. However, I argue here that there is still not enough evidence to confirm this proposed function. My argument is based on inference from several lines of observation and concern over several aspects of the past studies. First, ECM fungi mainly inhabit deeper soil horizons, in which the availability of carbon compounds with positive energetic value is low. Second, the ability of ECM fungi to produce ligninolytic enzymes and cellulases is much weaker than that of saprotrophic basidiomycetes. This is most apparent in the low copy abundance of corresponding genes in the sequenced genomes of ECM species Laccaria bicolor and Amanita bisporigenes compared to the saprotrophic species Galerina marginata. I offer alternative hypotheses to explain the past observations of increased enzyme activity during starvation periods. These include, the induction of autolytic processes in ECM fungal mycelia or an attack on the host tissues to support escape from a dying root and to allow for a search for new hosts.
Keywords: Starvation; lignin; hladovění; půda; Lignin; Carbon; kořeny rostlin; Genome, Fungal; Mycorrhizae; organické látky; Organic Chemicals; půdní mikrobiologie; Amanita; genom fungální; Soil; uhlík; mykorhiza; Plant Roots; Basidiomycota; Laccaria; Soil Microbiology